Study of surface flattening kinetics by low-energy electron diffraction on rutile(110). - Cai, Aiguo. (University of Ottawa (Canada), 2000)
In this thesis, we study the surface flattening kinetics at a roughened rutile (1 x 1)(110) surface in an ultrahigh vacuum chamber by low energy electron diffraction spot profile analysis (SPA-LEED). Surface roughness was introduced by argon ion bombardment at a low sputtering dose, instead of deposition such as molecular beam epitaxy (MBE) used elsewhere. In addition, we further investigated the effect of annealing on the terrace height distribution by measuring spot profiles versus incident electron energy at room temperature after annealing for different times. The terrace height distribution was determined by analyzing the relative weight of the Bragg peak in the spot profiles versus the incident electron energy. By means of the results of the terrace height distribution the interface width versus annealing time was determined. (Abstract shortened by UMI.)
Keywords: Physics, Condensed Matter.